Critical Analysis of Nursing Ethics and Professional Standards - Alanazi, Anwar Mohammed Suwayhan; Alshammari, Reem Ibrahim; Albariqi, Sundus Ali Ahmed; Alotaibi, Saud Madi Mesha; Alruwaili, Reem Musaad Sharidah; Alonezi, Amal Mayouf; Alshahrani, Ali Abdulwahab Hadhram; Alsamih, Wala Samih Nasser; alanazi, Eman tirad; alharbi, Hanadi hamoud (Journal of Ecohumanism, 2024)
Nursing has a robust system of ethics that directs the operations and productivity of its professionals about patients. Ethical principles in nursing and a code of ethics are applicable in determining nurses’ behaviour, decisions, and ethical concerns in clinical practice. This revised and expanded review synthesizes current literature about the ethical perspectives and relevant codes that inform the nursing profession, examines obstacles preventing compliance, and reviews the effects of ethical decisions on clients. Besides, the paper explores the dynamic aspect of nursing ethics about technologies, culture, and healthcare systems. The results indicate that there is a set of nursing ethics that guide nursing practice, but practical ethics experiences remain a challenge and, therefore, require constant training and counselling. The authors have concluded the paper with recommendations for how the ethics for nursing and professionalism of nursing could be developed more effectively so that the ethical requirements of the profession can be met in the context of the growing complexity of tomorrow’s healthcare system.